Development of canagliflozin nanocrystals sublingual tablets in the presence of sodium caprate permeability enhancer: formulation optimization, characterization, in-vitro, in silico, and in-vivo study - Sammar Fathy Elhabal; Mohamed A El-Nabarawi; Nashwa Abdelaal; Mohamed Fathi Mohamed Elrefai; Shrouk A. Ghaffar; Mohamed Mansour Khalifa; Passant M. Mohie; Dania S. Waggas; Ahmed Mohsen Elsaid Hamdan; Samar Zuhair Alshawwa; Essa M. Saied; Nahla A. Elzohairy; et al. (Drug Delivery, 2023)
AbstractCanagliflozin (CFZ) is a sodium-glucose cotransporter-2 inhibitor (SGLT2) that lowers albuminuria in type-2 diabetic patients, cardiovascular, kidney, and liver disease. CFZ is classified as class IV in the Biopharmaceutical Classification System (BCS) and is characterized by low permeability, solubility, and bioavailability, most likely attributed to hepatic first-pass metabolism. Nanocrystal-based sublingual formulations were developed in the presence of sodium caprate, as a wetting agent, and as a permeability enhancer. This formulation is suitable for children and adults and could enhance solubility, permeability, and avoid enterohepatic circulation due to absorption through the sublingual mucosa. In the present study, formulations containing various surfactants (P237, P338, PVA, and PVP K30) were prepared by the Sono-homo-assisted precipitation ion technique. The optimized formula prepared with PVP-K30 showed the smallest particle size (157 ± 0.32 nm), Zeta-potential (−18 ± 0.01), and morphology by TEM analysis. The optimized formula was subsequently formulated into a sublingual tablet containing Pharma burst-V® with a shorter disintegration time (51s) for the in-vivo study. The selected sublingual tablet improved histological and biochemical markers (blood glucose, liver, and kidney function), AMP-activated protein kinase (AMPK), and protein kinase B (AKT) pathway compared to the market formula, increased CFZ’s antidiabetic potency in diabetic rabbits, boosted bioavailability by five-fold, and produced faster onset of action. These findings suggest successful treatment of diabetes with CFZ nanocrystal-sublingual tablets.